Semaphorin 3A promotes the long-term persistence of human SVF-derived microvascular networks in engineered grafts - Schwager, Juan M.; Di Maggio, Nunzia; Grosso, Andrea; Rasadurai, Abeelan; Minder, Nadja; Hubbell, Jeffrey A.; Kappos, Elisabeth A.; Schaefer, Dirk J.; Briquez, Priscilla S.; Banfi, Andrea; Burger, Maximilian G. (Frontiers in Bioengineering and Biotechnology, 2024)
The stromal vascular fraction (SVF) of human adipose tissue is an attractive cell source for engineering grafts with intrinsic vascularization potential, as it is rich in vasculogenic progenitors.However, in order to maintain their functional perfusion it is important to promote the in vivo stabilization of newly assembled microvascular networks. We previously found that Semaphorin 3A (Sema3A) promotes the rapid stabilization of new blood vessels induced by VEGF overexpression in skeletal muscle. Here we investigated whether Sema3A could promote the assembly, connection to circulation and persistence of human SVF-derived microvascular networks in engineered grafts.Recombinant Sema3A was engineered with a transglutaminase substrate sequence (TG-Sema3A) to allow cross-linking into fibrin hydrogels. Grafts were prepared with freshly isolated human SVF cells in fibrin hydrogels decorated with 0, 0.1 or 100 µg/ml TG-Sema3A and implanted subcutaneously in immune-deficient mice. After 1 week in vivo, the assembly of human-derived networks was similar in all conditions. The outer part of the grafts was populated by blood vessels of both human and mouse origin, which formed abundant hybrid structures within a common basal lamina. About 90% of human-derived blood vessels were functionally connected to the host circulation in all conditions. However, in the control samples human vessels were unstable. In fact, they significantly regressed by 6 weeks and could no longer be found by 12 weeks. In contrast, a low Sema3A dose (0.1 µg/ml) promoted further human vascular expansion by about 2-fold at 6 weeks and protected them from regression until 12 weeks. From a mechanistic point of view, the stabilization of SVF-derived vessels by 0.1 µg/ml of Sema3A correlated with the recruitment of a specific population of monocytes expressing its receptor Neuropilin-1. In conclusion, Sema3A is a potent stimulator of in vivo longterm persistence of microvascular networks derived from human SVF. Therefore, decoration of matrices with Sema3a can be envisioned to promote the functional support of tissue engineered grafts.